Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.7567/jjap.55.030303
|View full text |Cite
|
Sign up to set email alerts
|

Observation of nanometer-sized crystalline grooves in as-grown β-Ga2O3 single crystals

Abstract: On the surface of as-grown β-Ga2O3 single crystals that are cut and polished, we found nanometer-sized grooves elongated in the [001] direction. We confirmed that these grooves terminate within the crystals in the [010] direction. This proves that the grooves are different from micropipes penetrating crystals. Their typical length and width are 50–1200 nm in the [001] direction and ∼40 nm in the [100] direction, respectively. The grooves tend to form an array in the [001] direction. The type of nanometer-sized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 18 publications
3
60
0
Order By: Relevance
“…16) Recently, we have found grooveshaped void defects in as-received (unetched) β-Ga 2 O 3 single crystals, whose typical length is in the range of 50-1200 nm in the [001] direction and approximately 40 nm in the [100] direction. 17) In Ref. 18, we named these groove-shaped void defects type-G defects.…”
Section: Introductionmentioning
confidence: 99%
“…16) Recently, we have found grooveshaped void defects in as-received (unetched) β-Ga 2 O 3 single crystals, whose typical length is in the range of 50-1200 nm in the [001] direction and approximately 40 nm in the [100] direction. 17) In Ref. 18, we named these groove-shaped void defects type-G defects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, acid etchants have been widely used in defect-selective etching. In 2016, Hanada et al 72 first demonstrated the groove-shaped defects (void-type) of β-Ga 2 O 3 , which were different from the previously reported micropipes. H 3 PO 4 was used to display the etch pits at 140 °C.…”
Section: Conventional Etchingmentioning
confidence: 83%
“…Among these, EFG has received much more attention and has recently become a major method for commercial production of β-Ga 2 O 3 wafers due to the accessibility of a relatively stable temperature field, especially at the liquid-solid interface. However, during the growth of a β-Ga 2 O 3 single crystal, some defects are usually inevitable in the bulk [31][32][33][34][35]. CZ has been regarded as another promising method for growing large high-quality β-Ga 2 O 3 single crystals.…”
Section: Introductionmentioning
confidence: 99%